Emerging Roles of Liquid–Liquid Phase Separation in Cancer: From Protein Aggregation to Immune-Associated Signaling - Lu, Jiahua; Qian, Junjie; Xu, Zhentian; Yin, Shengyong; Zhou, Lin; Zheng, Shusen; Zhang, Wu (Frontiers in Cell and Developmental Biology, 2021)
Liquid–liquid phase separation (LLPS) of proteins and nucleic acids has emerged as a new paradigm in cellular activities. It drives the formation of liquid-like condensates containing biomolecules in the absence of membrane structures in living cells. Typical membrane-less condensates such as nuclear speckles, stress granules and cell signaling clusters play important roles in various cellular activities, including transcription regulation, cellular stress response, and signaling transduction. Previous studies have elucidated the biophysical and biochemical principles underlying the formation of these liquid condensates and how these principles determine the molecular properties, LLPS behavior, and composition of liquid condensates. While the basic rules driving LLPS are increasingly being revealed, our understanding of their function in cellular activities is limited, especially in a pathological context. Here, we summarize the recent progress on the existing roles of LLPS in cancer research, including cancer-related signaling pathways, transcriptional regulation, and LLPS-derived proteins like p53, which aberrantly aggregates in cancer cells. In addition, we briefly introduce the basic rules for LLPS, and the cellular signaling that potentially implicated in cancers, such as pathways relevant to the immune response and autophagy.